Comparative study of Irish and Scottish logboats - Gregory, N. T. N. (The University of Edinburgh, 1997)
This thesis examines Irish logboats and compares them in detail to Scottish logboats. It catalogues extant and recorded Irish Logboats, and includes drawings and photographic records. All aspects of both countries' boats, such as their dimensions, form, and evidence for propulsion are examined and interpreted. Those logboats that have dating evidence are also examined and compared to literary and other sources. The distributions of the boats are compared to their geographical and archaeological contexts and emerging patterns explored in detail. The results of this study are investigated on a national and regional basis. The native tree species of Ireland and Scotland are considered with particular reference to those used to make the logboats as well as their availability during the demise of logboat use. In keeping with this, evidence for construction techniques is studied, as are their applications in logboat reconstructions. The logboat reconstructions are used with aspects of naval architecture to determine and compare the operational capabilities of logboats under differing load and propulsive conditions. Where applicable, the data which is discerned from the logboats' contexts, forms, dimensions and functional features are combined with aspects of the wood science and naval architecture to determine their original operational uses. Finally, this data is incorporated into an ongoing computer programme which enables the performance capabilities of other logboats, as yet undiscovered, to be determined.
A comparative study of Irish and Scottish logboats
Keywords: Logboats; experimental archaeology